PERANAN SEKTOR PERTANIAN DI SULAWESI UTARA - Ria A. Paendong; Lyndon R.J. Pangemanan; Theodora M. Katiandagho; Vicky R.B. Moniaga (Universitas Sam Ratulangi, 2015)
ABSTRACT Ria Angelina Paendong. Pernanan sektor pertanian di Sulawesi Utara. Under the guidance of Lyndon R.J Pangemanan (Chairman), Th Katiandagho (Members), dan Vicky R.B Moniaga (Members). The purpose of this study was to determine wheather the agricultural sector and sub-sector of agrigulture (crops, plantations, fisheries, foresty,) still as a commodity base. This research uses descriptive-analytic method. The data used are secondary data obtained from the office of the Central Bureau Of Statistics North Sulawesi. Measured variabel is the GDP and GDRP of North Sulawesi to find the value of LQ. LQ can determine wheather the value of the agricultural sector is still in the category of the base sector. In determining the value of LQ, measured variabels include the economics sector of GDRP last five years between 2008-2012 and the public sector of GDRP tramstop five years between the years 2008-2012, GDP of the agricultural sector and agricultural sub-sector GDP in the province of North Sulawesi. The ability of the agricultural sector into a base sector in North Sulawsi as supported by a large expanse of land resources which can be used as means of lands resources which can be used as a means of support to increase agricultural production. Based on LQ scores, agricultural sub-sector which is the base is plantation sub-sector and sub-sector of fishery. Keywords : Base, GDP, GDRP